DBU-Catalyzed Ring Expansion or Ene-amine Formation Involving δ-Acetoxy Allenoates and N-Sulfonyl Hydrazides - Khan, Shabbir Ahmed; Kumar, A. Sanjeeva; Swamy, K. C. Kumara (Organic letters, 2023)
DBU-catalyzed spiro-annulation and concomitant ring expansion/dominoreaction of delta-acetoxy allenoates with cycl-2-ene-N-sulfonyl hydrazides afford ring-expanded (5 -> 6, 6 -> 7, and 7 -> 8) products. By contrast, cycl-3-ene/ane-N-sulfonyl hydrazones under similar conditions deliver pyrazolecores with the same allenoate that involves allylic elimination inwhich delta-acetoxy allenoate serves as 3C-synthon. The key spirocyclicintermediates, as well as dienyl-amine intermediates, are isolatedand characterized. An extension to (R)-(-)-carvone-derivedsulfonyl hydrazide also led to ring expansion and gave pyrazoloazepine.